2023
DOI: 10.3390/biomedicines11102627
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA LNC-565686 Promotes Proliferation of Prostate Cancer by Inhibiting Apoptosis through Stabilizing SND1

Xuke Qin,
Jiacheng Zhong,
Lei Wang
et al.

Abstract: Long non-coding RNAs (lncRNAs), typically more than 200 nt long, cannot encode proteins, but can regulate gene expression. They play an indispensable role in the occurrence and progression of various cancers. The main purpose of this study is to discuss the role and mechanism of LNC-565686 in prostate cancer. First, we found an increased expression of LNC-565686 in prostate cancer cells using RNA sequencing, which was further verified using qRT-PCR. Then, catRAPID was used to find that LNC-565686 might regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…39 Another study revealed that the lncRNA LNC-565686 enhances the growth of prostate cancer by preventing programmed cell death through the stabilization of SND1. 41 Zheng et al 42 Additionally, SND1 plays an important role in vascularization. 43,44 Here, functional investigations demonstrated that increased expression of LINC00987 effectively inhibited the proliferation and VM of LUAD cells.…”
Section: Discussionmentioning
confidence: 99%
“…39 Another study revealed that the lncRNA LNC-565686 enhances the growth of prostate cancer by preventing programmed cell death through the stabilization of SND1. 41 Zheng et al 42 Additionally, SND1 plays an important role in vascularization. 43,44 Here, functional investigations demonstrated that increased expression of LINC00987 effectively inhibited the proliferation and VM of LUAD cells.…”
Section: Discussionmentioning
confidence: 99%